PENGEMBANGAN BUKU PEGANGAN GURU TAMAN KANAK-KANAK DALAM PEMBELAJARAN BAHASA JAWA - Suharti, Suharti (LITERA, 2013)
This study aims to: (1) identify the use of the Javanese language as a medium of instruction in kindergartens, (2) identify teachers’ and students’ Javanese competence, and (3) find out important aspects in Javanese learning that kindergarten students need which will be included in the teacher book. The subjects comprised teachers of kindergartens in 4 regencies and 1 city. The data were collected through observations, interviews, and documents. The data were qualitatively analyzed and the data trustworthiness was enhanced using the method and source triangulation techniques. The results show the following. (1) Javanese is used as an additional medium of instruction in several kindergartens and most of them use Indonesian. (2) Students’ Javanese competence is very low and teachers’ competence is relatively low because at home they use Indonesian mixed with Javanese vocabulary. (3) Important Javanese language aspects for kindergarten students are those related to politeness, environment introduction, clothing, traditional foods, arts, and customs.